John Verse by Verse. - Osborne, Grant R. (Ashland : Lexham Press, 2018)
John is at once the most complex and the easiest to understand of all the Gospels. If we want a young seeker or new believer to read something that is both clear and filled with the gospel and good basic theology, we give them the Gospel of John. And if we want to study an incredibly deep theological masterpiece that stretches the brightest mind, we open the Gospel of John. It is the most evangelistic account of Jesus' life and ministry, and it also gives the mature Christian deep theological truths to chew on. In John Verse by Verse, respected New Testament scholar Grant R. Osborne invites the reader to become caught up in the dramatic masterpiece of the Fourth Gospel. He writes, "If I were teaching a course in college or seminary on creative writing, John's Gospel would be set alongside Shakespeare as models of brilliant characterization and plot." It is perhaps Osborne's favorite book of the Bible, and enthusiasm for it shines on every page. The Osborne New Testament Commentaries, by respected professor and author Grant R. Osborne, are for people seeking a straightforward explanation of the text in its context, avoiding either oversimplification or technical complexity. Osborne brings out the riches of the New Testament, making each book accessible for pastors and all who consider themselves students of Scripture.
The Demand for a Sign (2:18)Jesus' Incredible Response (2:19); Their Misunderstanding and Its Correction (2:20-21); The Aftermath: Belief (2:22); Inadequate Faith Based on Signs (2:23-25); Nicodemus and the New Birth (3:1-21); Introduction: Nicodemus Comes at Night (3:1-2); First Dialogue: You Must Be Born Again (3:3-4); Second Dialogue: You Must Be Born of Water and Spirit (3:5-8); Thesis: Born of Water and Spirit (3:5); Clarification: Spirit-Controlled Rebirth (3:6-8); Jesus Confronts Nicodemus's Ignorance (3:9-12); Jesus Demonstrates His Heavenly Authority (3:13-15).
Print version record.
Commentary: Life and Light Confront the World (3:16-21).
eBooks on EBSCOhost
Keywords: Bible. -- Commentaries; Bible; RELIGION -- Biblical Studies -- Jesus, the Gospels & Acts; RELIGION -- Biblical Studies -- New Testament; Commentaries